2022
DOI: 10.1002/ccd.30415
|View full text |Cite
|
Sign up to set email alerts
|

Novel technique for transcatheter closure of sinus venosus atrial septal defect: The temporary suture‐holding technique

Abstract: Background: Transcatheter repair of sinus venosus atrial septal defect (SVASD) has become an alternative option to surgical repair. There are potential significant complications related to stent stability in the superior vena cava (SVC) and potential migration of the stent that need to be addressed. Therefore, the technique is still evolving.Objectives: To report results of a new modification "the suture technique" that improves safety profile of positioning and securing a covered stent in the SVC.Methods: Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…After abstract screening, 36 full‐text articles were evaluated, leading to the inclusion of 12 papers detailing transcatheter repairs involving ≥2 patients with SVASD. 2 , 3 , 4 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 There is a possibility that a few of these publications were derived from the same patient cohort. We made a deliberate decision against consolidating these findings into the overall systematic review to avoid double counting patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After abstract screening, 36 full‐text articles were evaluated, leading to the inclusion of 12 papers detailing transcatheter repairs involving ≥2 patients with SVASD. 2 , 3 , 4 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 There is a possibility that a few of these publications were derived from the same patient cohort. We made a deliberate decision against consolidating these findings into the overall systematic review to avoid double counting patients.…”
Section: Resultsmentioning
confidence: 99%
“…A comprehensive summary of the outcomes stemming from this analysis is provided in Table S3 . 2 , 3 , 4 , 50 , 51 , 52 , 53 , 54 , 55 , 56 The majority of studies reported data on adult patients, with 9 of 12 studies having a study population aged>18 years. The Cheatham‐platinum stent was the most commonly used implant.…”
Section: Resultsmentioning
confidence: 99%
“…Two different methods suggested to avoid caudal stent migration and embolization include using an anchoring stitch for the upper end of the covered stent from jugular vein access or suturing two stents together before deployment. [ 9 ] An anchor zone of at least 2 cm in the SVC is essential for the stability of the covered stent. [ 5 6 ]…”
Section: Discussionmentioning
confidence: 99%
“…The selection of the appropriate one (long stents, overlapping stents, temporary suture-holding technique, etc.) should depend on the individual clinical situation and the experience of the center [4].…”
Section: Article Informationmentioning
confidence: 99%